1988
DOI: 10.1099/0022-1317-69-11-2703
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Sequence Homology of Coat Proteins as a Basis for Identification and Classification of the Potyvirus Group

Abstract: SUMMARYAnalysis of the 136 possible pairings of the coat protein amino acid sequences from 17 strains of eight distinct potyviruses revealed a bimodal distribution of sequence homology. Distinct members of the group exhibited sequence homologies ranging from 38 to 71 ~ (average 54%) with major differences in the length and sequence of their N termini and high sequence homology in the C-terminal half of the coat proteins. In contrast strains of individual viruses exhibited sequence homologies of 90 to 99% (aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
159
0
5

Year Published

1989
1989
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 233 publications
(181 citation statements)
references
References 37 publications
17
159
0
5
Order By: Relevance
“…The comparison of PPV-SK68 and PVY-H showed two conserved regions in the genomic 3 -part (NIb, CP) consisting of 28 and 29 nt stretches with similarities of 96% and 93%, respectively. The observed similarities corresponded with the alignment data of Shukla and Ward (1988). Bujarski and Nagy (1996) showed for Brome mosaic virus that sequence similarities of at least 15 nt between RNA2 and RNA3 were sufficient to promote efficient RNA2/RNA3 recombination, while sequence identities of nine or fewer nucleotides reduced the level of detectable recombinants.…”
Section: Identification Of Identical Sequence Clusters Between Potyvisupporting
confidence: 83%
“…The comparison of PPV-SK68 and PVY-H showed two conserved regions in the genomic 3 -part (NIb, CP) consisting of 28 and 29 nt stretches with similarities of 96% and 93%, respectively. The observed similarities corresponded with the alignment data of Shukla and Ward (1988). Bujarski and Nagy (1996) showed for Brome mosaic virus that sequence similarities of at least 15 nt between RNA2 and RNA3 were sufficient to promote efficient RNA2/RNA3 recombination, while sequence identities of nine or fewer nucleotides reduced the level of detectable recombinants.…”
Section: Identification Of Identical Sequence Clusters Between Potyvisupporting
confidence: 83%
“…Due to its large size, the taxonomy of this group was not resolved until sequence data, and particularly capsid sequence data, clarified the classification. There is a bimodal distribution of coat protein sequence similarity, with known distinct potyviruses ranging in sequence similarity between 38-71% and known strains of given viruses ranging between 90-99% (Shukla & Ward, 1988). D. D. Shukla and coworkers have shown that comparative sequence analysis 0001-2803 © 1995 SGM of whole coat protein sequences can produce plausible phylogenetic trees of potyviruses (Rybicki & Shukla, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…We have shown recently that coat protein sequence data can be used to discriminate between distinct viruses and strains (Shukla & Ward, 1988). Distinct potyviruses have coat protein sequence identities of 38 to 71 ~o compared to 90 to 99~ for related strains (see Shukla & Ward, 1989a, for review).…”
Section: Introductionmentioning
confidence: 99%